Assignment 8

#$&*

course MTH 158

2/9 3

008. `* 8

*********************************************

Question: * R.8.12. Simplify the cube root of 54

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

The cube root of 54 is the same as the cube root of 27 * 2, or 3 times the cube root of 2.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * The cube root of 54 is expressed as 54^(1/3).

The number 54 factors into 2 * 3 * 3 * 3, i.e., 2 * 3^3. Thus

54^(1/3) = (2 * 3^3) ^(1/3)

= 2^(1/3) * (3^3)^(1/3)

= 2^(1/3) * 3^(3 * 1/3)

= 2^(1/3) * 3^1

= 3 * 2^(1/3), i.e.,

3 * cube root of 2.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * R.8.18. Simplify the cube root of (3 x y^2 / (81 x^4 y^2) ).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

The cube root of (3 x y^2 / (81 x^4 y^2) ) = (1/3x) * the cube root of (xy^2/xy^2) or 1. (1/3x) * 1 = (1/3x).

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

The cube root of (3 x y^2 / (81 x^4 y^2) ) is

(3 x y^2 / (81 x^4 y^2) ) ^ (1/3) =

(1 / (27 x^3) ) ^(1/3) =

1 / ( (27)^(1/3) * ^x^3^(1/3) ) =

1 / ( (3^3)^(1/3) * (x^3)^(1/3) ) =

1 / ( 3^(3 * 1/3) * x^(3 * 1/3) ) =

1 / (3 * x) =

1 / (3x).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * R.8.30. Simplify 2 sqrt(12) - 3 sqrt(27).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

2 sqrt(12) - 3 sqrt(27) = 4 sqrt (3) – 9 sqrt (3) = -5 sqrt (3)

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

2 sqrt(12) - 3 sqrt(27)

= 2 sqrt( 2*2*3) - 3 sqrt(3*3*3)

= 2 sqrt(2^2 * 3) - 3 sqrt(3^3)

= 2 sqrt(2^2) sqrt^3) - 3 sqrt(3^2) sqrt(3)

= (2 * 2 - 3 * 3) sqrt(3)

= (4 - 9) sqrt(3)

= -5 sqrt(3)

Extra Question: What is the simplified form of (2 sqrt(6) + 3) ( 3 sqrt(6)) and how did you get this result?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(2 sqrt(6) + 3) ( 3 sqrt(6)) = (2 sqrt(6)(3 sqrt(6)) + (3)(3 sqrt 6) = 6 sqrt (6) + 9 sqrt (6) = 9 sqrt (6)

confidence rating #$&*: 0

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

(2*sqrt(6) +3)(3*sqrt(6)) expands by the Distributive Law to give

(2*sqrt(6) * 3sqrt(6) + 3*3sqrt(6)), which we rewrite as

(2*3)(sqrt6*sqrt6) + 9 sqrt(6) =

(6*6) + 9sqrt(6) =

36 +9sqrt(6).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

I just got lost when writing the information out after seeing the result I better understand the problem and answer.

@& In your solution you were OK up to a point:

(2 sqrt(6) + 3) ( 3 sqrt(6)) = (2 sqrt(6)(3 sqrt(6)) + (3)(3 sqrt 6)

is correct but then, for example

(2 sqrt(6)(3 sqrt(6)) = 6 sqrt(6) * sqrt(6), not just 6 sqrt(6).

sqrt(6) * sqrt(6) = 6 so

6 sqrt(6) * sqrt(6) = 6 * 6 = 36

*@

Self-critique Rating: 3

*********************************************

Question: * R.8. Expand (sqrt(x) + sqrt(5) )^2

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(sqrt(x) + sqrt(5) )^2 = (sqrt(x)^2) + (sqrt(5)^2) = x + 5

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

(sqrt(x) + sqrt(5) )^2

= (sqrt(x) + sqrt(5) ) * (sqrt(x) + sqrt(5) )

= sqrt(x) * (sqrt(x) + sqrt(5) ) + sqrt(5) * (sqrt(x) + sqrt(5) )

= sqrt(x) * sqrt(x) + sqrt(x) * sqrt(5) + sqrt(5) * sqrt(x) + sqrt(5) * sqrt(5)

= x + 2 sqrt(x) sqrt(5) + 5.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

I didn’t distribute all factors. I separated at the beginning and that gave me an incorrect answer.

------------------------------------------------

Self-critique Rating:

*********************************************

Question:

* R.8.42. What do you get when you rationalize the denominator of 3 / sqrt(2) and what steps did you follow to get this result?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

I didn’t have this problem in the book, however when you rationalize the denominator you multiply 3 / sqrt(2) by (sqrt(2)) / (sqrt(2)). This gives us 3 sqrt(2) / 2

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Starting with 3/sqrt(2) we multiply numerator and denominator by sqrt(2) to get

(3*sqrt(2))/(sqrt(2)*sqrt(2)) =

(3 sqrt(2) ) /2.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * R.8.48. Rationalize denominator of sqrt(2) / (sqrt(7) + 2)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

sqrt(2) / (sqrt(7) + 2) = sqrt(2) / (sqrt(7) + 2) * sqrt(7) -2/ sqrt(7) -2 = sqrt(2) * (sqrt(7) - 2) / (sqrt(7) * sqrt(7) – 4) or 7 – 4. So the final answer is sqrt(2) * (sqrt(7) - 2) / 3

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

To rationalize the denominator sqrt(7) + 2 we multiply both numerator and denominator by sqrt(7) - 2.

We obtain

( sqrt(2) / (sqrt(7) + 2) ) * (sqrt(7) - 2) / (sqrt(7) - 2)

= sqrt(2) * (sqrt(7) - 2) / ( (sqrt(7) + 2) * ( sqrt(7) - 2) )

= sqrt(2) * (sqrt(7) - 2) / (sqrt(7) * sqrt(7) - 4)

= sqrt(2) * (sqrt(7) - 2 ) / (7 - 4)

= sqrt(2) * (sqrt(7) - 2 ) / 3.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

Extra Question: What steps did you follow to simplify (x^3)^(1/6) and what is your result, assuming that x is positive and expressing your result with only positive exponents?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I would multiply 3 and 1/6 to get one half. Then I would simply write x^1/2 or sqrt of x

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Express radicals as exponents and use the laws of exponents.

(x^3)^(1/6) =

x^(3 * 1/6) =

x^(1/2). **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * R.8.60. Simplify 25^(3/2).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

25^(3/2) = (sqrt of 25)^3 or 5^3= 125

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

25^(3/2) =

(5^2)^(3/2) =

5^(2 * 3/2) =

5^(2 * 3/2) =

5^3.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * R.8.72. Simplify and express with only positive exponents:

(xy)^(1/4) (x^2 y^2) ^(1/2) / (x^2 y)^(3/4).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

I wasn’t sure at all how to do this problem.

confidence rating #$&*: 0

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

(xy)^(1/4) (x^2 y^2) ^(1/2) / (x^2 y)^(3/4)

= x^(1/4) * y^(1/4) * (x^2)^(1/2) * y^2 ^ (1/2) / ( (x^2)^(3/4) * y^(3/4) )

= x^(1/4) * y^(1/4) * x^(2 * 1/2) * y^(2 * 1/2) / ( (x^(2 * 3/4) * y^(3/4) )

= x^(1/4) y^(1/4) * x^1 * y^1 / (x^(3/2) y^(3/4) )

= x^(1 + 1/4) y^(1 + 1/4) / (x^(3/2) y^(3/4) )

= x^(5/4) y^(5/4) / (x^(3/2) y^(3/4) )

= x^(5/4 - 3/2) y^(5/4 - 3/4)

= x^(5/4 - 6/4) y^(2/4)

= x^(-1/4) y^(1/2)

= y^(1/2) / x^(1/4).

STUDENT QUESTION

I wrote the entire given solution on paper to see how to solve, but I am still confused when it gets to the

= x^(1 + 1/4) y^(1 + 1/4) / (x^(3/2) y^(3/4)

How do you get 1 + ¼? Does the 1 come from the xy on the right of the numerator?

INSTRUCTOR RESPONSE

The numerator of the expression

x^(1/4) y^(1/4) * x^1 * y^1 / (x^(3/2) y^(3/4) )

contains two factors which are powers of x. The two are

x^(1/4) and x^1 (the latter could be written just as x, but to apply the laws of exponents it's not a bad idea to write the exponent explicitly).

When you multiply these two factors, the laws of exponent tell you that you get x^(1/4 + 1) = x^(5/4).

The same thing happens with the y factors.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

It all looks very simple after initially breaking the xy portions down. I believe that if I had known to do that I could’ve gotten the rest of the problem worked ok. As I watched and worked the given solution for myself it made perfect sense.

------------------------------------------------

Self-critique Rating: 3

*********************************************

Question: * R.8.84. Express with positive exponents:

( (9 - x^2) ^(1/2) + x^2 ( 9 - x^2) ^(-1/2) ) / (9 - x^2).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your Solution:

Again, I didn’t understand these problems either and could get no farther than writing the problem on paper.

confidence rating #$&*: 0

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

( (9 - x^2) ^(1/2) + x^2 ( 9 - x^2) ^(-1/2) ) / (9 - x^2) =

( (9 - x^2) ^(1/2) + x^2 / ( 9 - x^2) ^(1/2) ) / (9 - x^2) =

[ (9 - x^2) (1/2) / (9 - x^2)^1 ] + [ x^2 / ( (9 - x^2)^(1/2) * (9 - x^2)^ 1) ] =

(9 - x^2) ^(-1/2) + x^2 / (9 - x^2)^(3/2) =

1 / (9 - x^2)^(1/2) + x^2 / (9 - x^2)^(3/2).

In the third step the exponent ^1 on the (9 - x^2) expressions wasn't necessary, but was included to explicitly show the exponents and the application of the laws of exponents.

The first term in the 4th step is obtained as follows:

(9 - x^2) (1/2) / (9 - x^2)^1 = (9 - x^2) ^ (1/2 - 1) = (9 - x^2)^(-1/2).

EXPANDED EXPLANATION OF STEPS

( (9 - x^2) ^(1/2) + x^2 ( 9 - x^2) ^(-1/2) ) / (9 - x^2) =

( (9 - x^2) ^(1/2) + x^2 / ( 9 - x^2) ^(1/2) ) / (9 - x^2)

In the above step we have replace (9 - x^2) ^ (-1/2) in the numerator by (9 - x^2)^(1/2) in the denominator, following the rule that a^-b = 1 / (a^b) with a = (9 - x^2) and b = 1/2.

( (9 - x^2) ^(1/2) + x^2 / ( 9 - x^2) ^(1/2) ) / (9 - x^2) =

[ (9 - x^2) (1/2) / (9 - x^2)^1 ] + [ x^2 / ( (9 - x^2)^(1/2) * (9 - x^2)^ 1) ]

The above step is just the distributive law of multiplication over addition, in which we multiply through the expression ( (9 - x^2) ^(1/2) + x^2 / ( 9 - x^2) ^(1/2) ) by 1 / (9 - x^2). The brackets [ ] have been added to clarify the two terms in the resulting expression, but the expression has the same meaning without them.

[ (9 - x^2) (1/2) / (9 - x^2)^1 ] + [ x^2 / ( (9 - x^2)^(1/2) * (9 - x^2)^ 1) ] =

(9 - x^2) ^(-1/2) + x^2 / (9 - x^2)^(3/2)

(9 - x^2) ^ (1/2) / (9 - x^2)^2 = (9 - x^2)^-1/2, by the laws of exponents; and (9 - x^2)^(1/2) * (9 - x^2) = (9 - x^2) ^(3/2) by the laws of exponents.

(9 - x^2) ^(-1/2) + x^2 / (9 - x^2)^(3/2) =

1 / (9 - x^2)^(1/2) + x^2 / (9 - x^2)^(3/2)

(9 - x^2) ^(-1/2) has been replaced by 1 / (9 - x^2) ^(1/2), using a^-b = 1 / a^b.

All the exponents in the final expression are positive.

It would also be possible to factor out 1 / (9 - x^2)^(1/2), though this wasn't requested and isn't necessary in the problem as stated. The result would be

1 / (9 - x^2)^(1/2) * ( 1 + x^2 / (9 - x^2) ).

This could be further simplified to

1 / (9 - x^2)^(1/2) * ( 9 / (9 - x^2) ) , which is equal to

9 / (9 - x^2)^(3/2)

You aren't expected to be able to read these expressions. You are expected to be able to write them out in standard form; having done so you should understand.

However these expressions are fairly challenging, so some of the expressions will be depicted here

( (9 - x^2) ^(1/2) + x^2 ( 9 - x^2) ^(-1/2) ) / (9 - x^2) would be depicted in standard notation as

(9 - x^2) ^(-1/2) + x^2 / (9 - x^2)^(3/2) would be depicted in standard notation as

1 / (9 - x^2)^(1/2) + x^2 / (9 - x^2)^(3/2) would be depicted in standard notation as

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

It is beginning to make a little more sense to me but I am only getting the numbers down and not necessarily the logic behind manipulating the numbers.

@& You need to start with the definition of a negative exponent:

a^-b = 1 / a^b.

Thus, for example, 2^-3 = 1 / 2^3 = 1/8.

Or (x + 2 y) ^(-2) = 1 / (x + 2 y)^2.

The first part of the expanded explanation of the steps reads as follows:

( (9 - x^2) ^(1/2) + x^2 ( 9 - x^2) ^(-1/2) ) / (9 - x^2) =

( (9 - x^2) ^(1/2) + x^2 / ( 9 - x^2) ^(1/2) ) / (9 - x^2)

In the above step we have replace (9 - x^2) ^ (-1/2) in the numerator by (9 - x^2)^(1/2) in the denominator, following the rule that a^-b = 1 / (a^b) with a = (9 - x^2) and b = 1/2.

Let me know what you do and do not understand about this step.

If you do understand this, I believe you'll get it. However look at the next step, etc., and let me know what you do and do not understand.*@

------------------------------------------------

Self-critique Rating: 1

*********************************************

Question: * R.8.108. v = sqrt(64 h + v0^2); find v for init vel 0 height 4 ft; for init vel 0 and ht 16 ft; for init vel 4 ft / s and height 2 ft.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your Solution:

This problem wasn’t assigned, however it’s a simple chug-and-plug problem. For part a, the first object with height of 4 and final velocity of 0 v =sqrt(64*4 + 0) or sqrt (256)= 16 feet per second. In part b, v = sqrt(64*16 + 0) or sqrt (1024)= 32 feet per second. In part c, v = sqrt(64*2 + 16) or sqrt (144)= 12 feet per second.

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

If initial velocity is 0 and height is 4 ft then we substitute v0 = 0 and h = 4 to obtain

• v = sqrt(64 * 4 + 0^2) = sqrt(256) =16.

If initial velocity is 0 and height is 16 ft then we substitute v0 = 0 and h = 4 to obtain

• v = sqrt(64 * 16 + 0^2) = sqrt(1024) = 32.

Note that 4 times the height results in only double the velocity.

If initial velocity is 4 ft / s and height is 2 ft then we substitute v0 = 4 and h = 2 to obtain

• v = sqrt(64 * 2 + 4^2) = sqrt(144) =12.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating:ok

Extra Question: What is the simplified form of (24)^(1/3) and how did you get this result?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(24)^(1/3) = cubed root of 24 =cube root of (8 * 3) or 2 * cube root of 2

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * (24)^(1/3) =

(8 * 3)^(1/3) =

8^(1/3) * 3^(1/3) =

2 * 3^(1/3) **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question:

Extra Question: What is the simplified form of (x^2 y)^(1/3) * (125 x^3)^(1/3) / ( 8 x^3 y^4)^(1/3) and how did you get this result?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(x^2 y)^(1/3) * (125 x^3)^(1/3) / ( 8 x^3 y^4)^(1/3) =

(125x^5y)^(1/3) / (8 x^3 y^4)^(1/3) = 125x^2 / 8y^3

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * (x^2y)^(1/3) * (125x^3)^(1/3)/ ( 8 x^3y^4)^(1/3)

(x^(2/3)y^(1/3)* (5x)/[ 8^(1/3) * xy(y^(1/3)]

(x^(2/3)(5x) / ( 2 xy)

5( x^(5/3)) / ( 2 xy)

5x(x^(2/3)) / ( 2 xy)

5 ( x^(2/3) ) / (2 y) **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

I got lost at the very beginning and made mistakes that caused me to really mess the problem up. I am understanding more but at a very slow pace as I go along with these radicals.

@& You were OK up through

(x^2 y)^(1/3) * (125 x^3)^(1/3) / ( 8 x^3 y^4)^(1/3) = (125x^5y)^(1/3) / (8 x^3 y^4)^(1/3)

You could have then written

( (125x^5y) / (8 x^3 y^4) )) ^ (1/3)

and simplified to get

( 125 x^2 / (8 y^3) ) ^(1/3)

which is then equal to

125^(1/3) * x^2^(1/3) / ( (8^(1/3) * (y^3)^1/3) )

which then simplifies to

5 * x^(2/3) / (2 * y).

Let me know what you do and do not understand, and I'll try to clarify further.

*@

------------------------------------------------

Self-critique Rating: 2

*********************************************

Question: Extra question. What is the simplified form of sqrt( 4 ( x+4)^2 ) and how did you get this result?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

sqrt( 4 ( x+4)^2 ) = sqrt (4(x^2 + 16)) = sqrt (4x^2 + 64) = 2x + 8 or 2(x + 4)

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

We use two ideas in this solution:

• sqrt(a b) = sqrt(a) * sqrt(b) and

• sqrt(x^2) = | x |

To understand why sqrt(x^2) = | x | and not just x consider the following:

• Let x = 5. Then sqrt(x^2) = sqrt( 5^2 ) = sqrt(25) = 5, so sqrt(x^2) = x.

It is also clear that in this case, | x | = | 5 | = 5, so | x | = x, and we can say that sqrt(x^2) = | x |.

• Now let x = -5. We get sqrt(x^2) = sqrt( (-5)^2 ) = sqrt(25) = 5.

In this case sqrt(x^2) = 5 but x is not equal to 5, so sqrt(x^2) is not x.

However, in this case | x | = | -5 | = 5, so it is the case the sqrt(x^2) = | x |.

Using these ideas we get

• sqrt( 4 ( x+4)^2 ) = sqrt(4) * sqrt( (x+4)^2 ) = 2 * | x+4 | **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

@& I've inserted some notes. If they get you straight, fine. If not, you're welcome to respond as indicated.*@